Direct Femtosecond Laser Printing of Silk Fibroin Microstructures - Santos, Moliria V.; Paula, Kelly T.; De Andrade, Marcelo B.; Gomes, Emmanuel M.; Marques, Lippy F.; Ribeiro, Sidney J. L. [UNESP]; Mendonça, Cleber R. (American Chemical Society (ACS), 2020)
Fabrication of functional silk fibroin microstructures has extensive applications in biotechnology and photonics. Considerable progress has been made based on lithographic methods and self-assembly approaches. However, most methods require chemical modification of silk fibroin, which restricts the functionalities of the designed materials. At the same time, femtosecond laser-induced forward transfer (fs-LIFT) has been explored as a simple and attractive processing tool for microprinting of high-resolution structures. In this paper, we propose the use of LIFT with fs-pulses for creating high-resolution structures of regenerated silk fibroin (SF). Furthermore, upon adding Eu3+/Tb3+ complexes to SF, we have been able to demonstrate the printing by LIFT of luminescent SF structures with a resolution on the order of 2 μm and without material degradation. This approach provides a facile method for printing well-defined two-dimensional (2D) micropatterns of pure and functionalized SF, which can be used in a wide range of optical and biomedical applications.
Keywords: direct laser printing; femtosecond laser; lanthanides β-diketonate complex; LIFT; luminescence; microprinting; rare earth; silk fibroin